2016
DOI: 10.1093/aob/mcv185
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between root diameter, root length and root branching along lateral roots in adult, field-grown maize

Abstract: Background and Aims Root diameter, especially apical diameter, plays an important role in root development and function. The variation in diameter between roots, and along roots, affects root structure and thus the root system's overall foraging performance. However, the effect of diameter variation on root elongation, branching and topological connections has not been examined systematically in a population of high-order roots, nor along the roots, especially for mature plants grown in the field.Methods A met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 68 publications
12
61
1
Order By: Relevance
“…Previous efforts to classify lateral roots in cereal species have been reported Watt et al, 2008;Rebouillat et al, 2009;Henry et al, 2016;Passot et al, 2016), but these classifications were often based on anatomical traits, mainly root diameter and vasculature. A first difficulty comes from the fact that some morphological traits change along lateral roots, typically root diameter (Wu et al, 2016), which was confirmed in our maize data. A different classification method, based on growth rates, was reported in rice (Rebouillat et al, 2009), for which growth rates were highly contrasting among lateral roots but assignment to classes was based on expert knowledge.…”
Section: A New Longitudinal Data Analysis Approach To Identify Laterasupporting
confidence: 52%
See 1 more Smart Citation
“…Previous efforts to classify lateral roots in cereal species have been reported Watt et al, 2008;Rebouillat et al, 2009;Henry et al, 2016;Passot et al, 2016), but these classifications were often based on anatomical traits, mainly root diameter and vasculature. A first difficulty comes from the fact that some morphological traits change along lateral roots, typically root diameter (Wu et al, 2016), which was confirmed in our maize data. A different classification method, based on growth rates, was reported in rice (Rebouillat et al, 2009), for which growth rates were highly contrasting among lateral roots but assignment to classes was based on expert knowledge.…”
Section: A New Longitudinal Data Analysis Approach To Identify Laterasupporting
confidence: 52%
“…sunflower [Helianthus annuus]; Aguirrezabal et al, 1994), annual monocots (e.g. maize [Zea mays]; Jordan et al, 1993;Wu et al, 2016), and perennials (oak [Quercus robur]; Pagès, 1995; rubber tree [Hevea brasiliensis]; Thaler and Pagès, 1996;and banana [Musa acuminata]; Lecompte et al, 2005). It also has been observed in the model species Arabidopsis (Arabidopsis thaliana; Freixes et al, 2002).…”
mentioning
confidence: 95%
“…For example, a greenhouse study on winter wheat at the preflowering stage showed that total root length correlated negatively with root diameter (Awad, Byrne, Reid, Comas, & Haley, ). Likewise, a field‐based study in maize found that diameter decreased along the root and change in diameter was correlated with length (Wu, Pages, & Wu, ). However, the average root diameter reported in this study was consistent with the 0.14–0.30 mm range of fibrous wheat root system reported by Manschadi, Manske, and Vlek ().…”
Section: Discussionmentioning
confidence: 95%
“…The vigor factor can also scale the root‐specific root diameter to allow an allometric relation between elongation rate and root diameter expansion within a root class (Pagès, 2000; Wu et al ., 2016). The initial root diameter is otherwise a root class‐specific input parameter.…”
Section: Methodsmentioning
confidence: 99%
“…The elongation rates of individual roots are predefined in the parameter space, but may be scaled according to a 'root vigor' scaling factor, for example, drawn from a lognormal distribution of elongation rates (scaled to unity), thus creating variation in length. The vigor factor can also scale the root-specific root diameter to allow an allometric relation between elongation rate and root diameter expansion within a root class (Pag es, 2000;Wu et al, 2016). The initial root diameter is otherwise a root classspecific input parameter.…”
Section: Researchmentioning
confidence: 99%